Painéis aglomerados produzidos com resíduos de marcenaria - Alexandre, Bárbara Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
The aim of this work was evaluate the technical viability of hand pressed particleboard production using wood residues from Massaranduba (Manilkara sp.) or the mix of three Caatinga species (Pereiro (Aspidosperma pyrifolium), Sabiá (Mimosa caesalpiniifolia) e PauBranco (Auxemma oncocalyx)) and PVA adhesive. Physical, mechanical and thermal resistance of the residue particleboards were evaluated and compared with commercial melamine one faced particleboard. The research began with the boards formation of 0.60 g/cm3 target density and 35 x 30 x 1.5 cm size, using 737g of particles and 220g of adhesive. The pressing was manual, using clamps and, after two days, the boards were removed from the mould and cut to obtain proper specimens to test. Boards made from different residues showed statistic difference densities among them. Caatinga residues boards showed density of 0.31 g/cm3 and the ones made from Massaranduba, 0.36 g/cm3. Based on the tests results, compared with commercial particleboards, it could be observed that the manufactured board showed better results of thickness swelling and water absorption. Also, it could be observed that the particleboards were good thermal insulating material.
Monografia
Keywords: Adesivo PVA; Prensagem manual; Condutividade térmica; Caatinga; PVA adhesive; Manual pressing; Thermal conductivity; Caatinga; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL